A study on maximizing the utilization of fleet in order to operate at the lowest cost by road feeder service of Sri Bayanaemas / Asraf Ahmad - Asraf, Ahmad (Faculty of Business and Management, 1993)
Freight industry exist with their main objective i s to support the world of distributio one can be c a t e g o r i e s under the general handling of i n d u s t r i a l engineering where i t concerned more with the p r a c t i c a l a p p l i c a t i o n and method of approaching the d i s t r i b u t i o n such as in running the warehouses and transport f l e e t s , the select i o n and use of materials handling equipment, packaging, documentation and others.